2016
DOI: 10.1016/j.ssresearch.2015.12.002
|View full text |Cite
|
Sign up to set email alerts
|

History, place, and racial self-representation in 21st century America

Abstract: How is a person’s racial self-representation related to the race history of the place in which he or she lives? We use Census Bureau data about race and ancestry to address this research question for two groups of people with mixed racial heritage: those reporting white and American Indian heritages, or reporting black and American Indian heritages. Links between history, place, and self-representation can be seen in geographic clustering for each race/ancestry response combination. We use multinomial logistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Outside of rural and high American Indian population density contexts, American Indian racial group membership is questioned (Jacobs ). Social definitions of American Indian racial group membership are not shaped only by physical characteristics or ancestry as some might believe, but also regional demographic characteristics (Liebler and Zacher ). This particular case of racial contestation also illustrates fluidity in racial definitions—internal migration from one US region to another can lead to an altogether different social experience of race (Newby and Dowling ).…”
Section: Moving Forward: Racial Identity Contestation As a Tool For Bmentioning
confidence: 99%
“…Outside of rural and high American Indian population density contexts, American Indian racial group membership is questioned (Jacobs ). Social definitions of American Indian racial group membership are not shaped only by physical characteristics or ancestry as some might believe, but also regional demographic characteristics (Liebler and Zacher ). This particular case of racial contestation also illustrates fluidity in racial definitions—internal migration from one US region to another can lead to an altogether different social experience of race (Newby and Dowling ).…”
Section: Moving Forward: Racial Identity Contestation As a Tool For Bmentioning
confidence: 99%
“…However, a growing number of studies show that racial categorization can be fickle. People can experience changes in racial categorization as they progress over the life course and/or as they move through various social contexts, such as between school and home (Alba et al, 2016;Bratter & O'Connell, 2017;Harris & Sim, 2002;Holloway et al, 2009;Liebler et al, 2017;Liebler & Zacher, 2016;Mason, 2017;Reece, 2019aReece, , 2019bReece, , 2019cSaperstein & Penner, 2010. These microlevel racial shifts show that race is not as neat as Americans often imagine, and pave the way to interrogate, and possibly predict, macrolevel changes in the racial structure.…”
Section: Introductionmentioning
confidence: 99%
“…Research also shows that racial categorization can be highly contingent within the same country at the same point in time, such that people with similar characteristics may be categorized differently depending on where they live. For example, Liebler and Zacher (2016) showed that place-specific history, such as residing in American Indian territory or a former Confederate slave state, is related to racial identification. Similarly, Bratter and O’Connell (2017) found that living in a state with a history of antimiscegenation laws, living in areas with high Black relative to White poverty, or living in a highly diverse state increases the probability that parents will identify their biracial children only as “Black.” Americans are also more likely to classify their neighbors in ways that “match” the predominant racial category in their local area (Porter et al 2015), suggesting that a person may be perceived differently in different parts of the country.…”
Section: Introductionmentioning
confidence: 99%
“…We join this trend by using restricted-use geocoded data to explore racial classification, seeking to understand how this process may vary by place. Previous research has demonstrated the importance of place in patterns of racial categorization, showing how both historical context and contemporary population composition play a role in how people racially identify or are racially classified (e.g., Bratter and O’Connell 2017; Liebler and Zacher 2016; Porter, Liebler, and Noon 2015). We take that observation one step further, relaxing the assumption that the characteristics of places will have consistent associations throughout the country.…”
mentioning
confidence: 99%